CORRELATION BETWEEN FOOD QUALITY AND MICROBIOTA PROFILE OF PREGNANT WOMEN IN THE CITY OF PADANG : FOOD QUALITY AND MICROBIOTA PROFILE - Sary, Rizka Yulia; Helmizar, Helmizar; Putra, Andani Eka (STIKes Mandala Waluya Kendari, 2025)
Background: Pregnancy is a complex physiological period that requires systemic adaptation of the body. During pregnancy, a balanced blood microbiota plays an important role in maintaining the mother's immune system and supporting fetal development. This study aims to determine the correlation between food quality and the microbiota profile of pregnant women in Padang City. Methods: This is an observational study with a cross-sectional design. The study was conducted from January to March 2025 at the Centre for Diagnostic and Research on Infectious Diseases (PDRPI) Laboratory, Andalas University. The sample size was 20 participants, selected using total sampling. Microbiota profiling was performed using 16S rRNA metagenomic sequencing. The results of the microbiota profile analysis were analyzed using Microbiome Analysist software. Results: Statistical analysis showed a p-value of 0.14702 and a t-statistic of -1.5182, indicating that there was no statistically significant difference between food quality and microbiota profile. The comparison of the Firmicutes/Bacteroidetes ratio (F/B ratio) was 1.06, indicating a balanced microbiota in pregnant women. Conclusion: Although not statistically significant, these differences in microbiota composition are biologically important and suggest a potential association between dietary patterns and systemic health in pregnant women.